2003
DOI: 10.1556/aphyt.38.2003.1-2.19
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Tolerance and Predatory Strategy of Pit-Building Ant-Lion Larvae (Neuroptera: Myrmeleontidae)

Abstract: This study focuses on the nocturnal and diurnal temperature relations inside and around the pits of Myrmeleon bore pit-building ant-lion larvae living in unsheltered microhabitat and Euroleon nostras living in sheltered microhabitat. The larvae's potential hunting activity and prey handling phase of predation in relation to the temperature conditions were observed. Due to the structure of pitfalls and the thermal layers above and under the sand surface, the larvae must suffer less temperature fluctuation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Our study species were previously demonstrated to experience differing levels of temperature fluctuations in nature, that is, relatively higher in M. bore and lower in E. nostras ( Lackinger 1973 ; Abraham 2003 ). Additionally, both of these species show an increase in some activity parameters at 35 °C when compared with lower temperatures ( Klokočovnik et al 2016 ; Antoł et al 2018 ).…”
Section: Introductionmentioning
confidence: 90%
“…Our study species were previously demonstrated to experience differing levels of temperature fluctuations in nature, that is, relatively higher in M. bore and lower in E. nostras ( Lackinger 1973 ; Abraham 2003 ). Additionally, both of these species show an increase in some activity parameters at 35 °C when compared with lower temperatures ( Klokočovnik et al 2016 ; Antoł et al 2018 ).…”
Section: Introductionmentioning
confidence: 90%
“…Microclimate can play an important role in pit-building decisions, e.g. shade (Topoff, 1977;Scharf et al, 2008c), photoperiod (Scharf et al, 2008c), soil temperature (Geiler, 1966;Marsh, 1987;Ábrahám, 2003), rain and soil moisture (Gotelli, 1993;Morrison, 2004).…”
Section: Preference For Different Sands Of Various Particle Sizes In mentioning
confidence: 99%
“…In addition, building larger cone-shaped traps in response to stronger solar radiation might signify thermoregulatory behavior. Indeed, the base of pitfall traps has been shown to provide larvae with lower mean temperatures and reduced thermal fluctuations compared to the upper surface of the sand, where larvae establish their traps (Green 1955 ; Marsh 1987 ; Abraham 2003 ). In our experiment, we heated a layer of sand from the bottom, which means that by choosing to build a larger trap, a larva was closer to a heat source than a larva building a smaller trap.…”
Section: Discussionmentioning
confidence: 99%
“…To address the effects of the thermal environment on antlion hunting, we conducted a laboratory experiment on trap building in Myrmeleon bore larvae along an ecologically relevant thermal gradient. Although M. bore has been used to study antlion feeding biology and trap establishment (Matsura 1986 , 1987 ; Matsura and Takano 1989 ; Abraham 2003 ; Matsura et al 2005 ), thermal biology has never been studied in this species. We tested two competing hypotheses.…”
Section: Introductionmentioning
confidence: 99%